Dasar-Dasar Ideal dan Operasional dalam Pendidikan Islam - Riyadi, Ahmad (Dinamika Ilmu, 2011)
Basic Education in Islam can be distinguished on the basis of Ideal and Operational; Basic ideal of Islamic education is identical with the teachings of Islam, which is derived from the Qur'an and the Hadith. Al-Quran and Hadith are understood by the scholars in the ijtihad and qiyas. In essence, the Qur'an is discusse about human culture. Furthermore, it contains truth in line with the truth that is acceptable logically and historical evidence. This truth contains the essential truth more than speculative and relative truth. Basic operations are the foundation that is formed as the actuality of the basic ideal: the historical basic, social basic, economic basic, political and administrative base, psychological basic and philosophical basic.